Philosophical and theological writings - Lessing, Gotthold Ephraim, 1729-1781.; Nisbet, H. B. (Hugh Barr) (Cambridge, UK ; New York : Cambridge University Press, 2005)
This volume presents the most comprehensive collection to date in English of Lessing's philosophical and theological writings, several of which appear here in English for the first time. They are translated and edited by H.B. Nisbet, who also provides an introduction that sets them in their historical and philosophical contexts.
The Christianity of reason -- On the reality of things outside God -- Spinoza only put Leibniz on the track of [his theory of] pre-established harmony -- On the origin of revealed religion -- Leibniz on eternal punishment -- [Editorial commentary on the 'Fragments' of Reimarus] -- On the proof of the spirit and of power -- The testament of St. John -- A rejoinder -- A parable -- Axioms -- New hypothesis on the evangelists as merely human historians -- Necessary answer to a very unnecessary question of Herr Hauptpastor Goeze of Hamburg -- The religion of Christ -- That more than five senses are possible for human beings -- Ernst and Falk : dialogues for Freemasons -- The education of the human race -- [Recollections of conversations with Lessing in July and August 1780 / Friedrich Heinrich Jacobi.
Includes bibliographical references (pages xi-xii) and index.
Translated from the German.
Print version record.
eBooks on EBSCOhost
Keywords: Leibniz, Gottfried Wilhelm, -- Freiherr von, -- 1646-1716.; Philosophical theology; Protestant churches -- Doctrines -- Early works to 1800.; Philosophy, German -- 18th century -- Early works to 1800.; Philosophical anthropology -- Early works to 1800.; Philosophical theology; Églises protestantes -- Doctrines -- Ouvrages avant 1800.; Philosophie allemande -- 18e siècle -- Ouvrages avant 1800.; Anthropologie philosophique -- Ouvrages avant 1800.; Théologie philosophique; PHILOSOPHY -- History & Surveys -- Modern; Protestant churches -- Doctrines; Philosophy, German; Philosophical anthropology; Philosophical theology; 1700-1799; Early works